DONGENG SEBAGAI ALTERNATIF TKI MENGENALI MASYARAKAT KOREA - Ronidin Ronidin (Universitas Andalas, 2017)
This article discusses Korean tales that can be an alternative for Tenaga Kerja Indonesian (TKI) to recognize Korean society. These fairy tales are literary products that actually reflect the socio cultural reality of Korean society. The tales that are the source of data are download from the rubric of